Finding One's Path Into Another Language: On the Expression of Boundary Crossing by English Learners of French. Issue 1 (February 2015) - Hendriks, Henriette; Hickmann, Maya; Bylund, Emanuel; Athanasopoulos, Panos
<x xml:space="preserve">Abstract</x> Languages vary considerably in how they represent motion. One major source of variation (Talmy, 2000) depends on whether linguistic systems lexicalize path in the verb (verb‐framed languages) or in satellites (satellite‐framed languages). This typological difference involves more than different verb types in that it also affects elements outside the verb. The current study is concerned with the implications of such typological properties for second language learning, specifically studying speakers of a satellite‐framed language (English) acquiring a verb‐framed language (French). We hypothesize that typological differences between source and target languages should present some difficulties to learners. For English learners of French, an additional difficulty should result from the fact that French is not entirely consistent in its patterning, allowing English‐like lexicalization patterns in some cases, but not in others. This requires the learners to discover the nature of the regularities from a target input that presents them with constrained variability.